2007
DOI: 10.1074/jbc.m609657200
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Roles of Active Site Residues in the 3′-5′ Exonuclease of the Werner Syndrome Protein

Abstract: Werner syndrome is a human autosomal recessive disorder and is associated with premature aging and an increased incidence of cancer (1, 2). Werner syndrome patients exhibit an increased predisposition to arteriosclerosis, osteoporosis, type II diabetes mellitus, and a variety of tumors, which are normally observed during aging (2, 3). Fibroblast cultures from Werner syndrome patients show a reduced life span and a variety of chromosomal abnormalities including reciprocal translocations, deletions, and inversio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…In order to examine branch migration activity of the wild type WRN protein preparation in the absence of digestion, we suppressed the WRN exonuclease activity by decreasing the free Mg 2+ concentration. Since the WRN exonuclease acts by a two-metal ion dependent mechanism, free divalent cations are required to bind the exonuclease active site [43][45]. While WRN helicase remains active at Mg 2+ ∶ATP ratios near 1 [43](data not shown), we found that WRN exonuclease activity is highly dependent on the free Mg 2+ concentration.…”
Section: Resultsmentioning
confidence: 65%
“…In order to examine branch migration activity of the wild type WRN protein preparation in the absence of digestion, we suppressed the WRN exonuclease activity by decreasing the free Mg 2+ concentration. Since the WRN exonuclease acts by a two-metal ion dependent mechanism, free divalent cations are required to bind the exonuclease active site [43][45]. While WRN helicase remains active at Mg 2+ ∶ATP ratios near 1 [43](data not shown), we found that WRN exonuclease activity is highly dependent on the free Mg 2+ concentration.…”
Section: Resultsmentioning
confidence: 65%
“…Our results suggest that WRN interacts with the non-digested strand when degrading the opposite strand, consistent with the ring model of WRN exonuclease proposed by Perry et al (24), where both DNA strands appear to contact the exonuclease domain. Furthermore, the mouse WRN exonuclease appears to work as a multimer (65). As there is no information currently available regarding the structure of WRN exonuclease binding longer double-stranded DNA substrates, more studies are required to fully explain our results.…”
Section: Discussionmentioning
confidence: 99%
“…Solar cells were made of composites of poly(3-hexylthiophene) (P3HT) and a fullerene derivative and their high performance was found to depend on the structure and orientation of the P3HT matrix through detailed GIXS analysis [9]. Furthermore, SAXS studies were extended for the structural analysis of proteins and polynucleic acids in various conditions including in nature and complexes with diverse ligands including drugs [10][11][12][13][14].…”
Section: Small-angle X-ray Scatteringmentioning
confidence: 99%